Linalool Prevents Cisplatin Induced Muscle Atrophy by Regulating IGF-1/Akt/FoxO Pathway - Zhang, Hong; Chi, Mengyi; Chen, Linlin; Sun, Xipeng; Wan, Lili; Yang, Quanjun; Guo, Cheng (Frontiers in Pharmacology, 2020)
Skeletal muscle atrophy is an important feature of cancer cachexia, which can be induced by chemotherapy, and affects the survival and quality of life of cancer patients seriously. No specific drugs for cancer cachexia have been applied in clinical practice. This study explored the therapeutic effect of linalool (LIN) on cisplatin (DDP) induced skeletal muscle atrophy. In vivo, LIN can improve skeletal muscle weight loss, anorexia, muscle strength decline and other cachexia symptoms caused by cisplatin treatment in a Lewis lung cancer tumour bearing mouse model, and cause no adverse effects on the anti-tumour effect. LIN treatment decreased the expression of muscle RING-finger protein-1 (MuRF1) and Atrogin1(MAFbx) in muscle, and the activation of insulin-Like growth factor-1 (IGF-1)/ protein kinase B (Akt)/ forkhead box O (FoxO) pathway was observed. In vitro, LIN alleviated DDP induced C2C12 myotube atrophy, and IGF-1 receptor inhibitor Picropodophyllin (PIC), which had no adverse effect on C2C12 myotube cells, could reverse the protective effect of LIN. These results indicate that LIN down-regulates the expression of Atrogin1 and MuRF1 through the IGF-1/Akt/FoxO pathway, alleviating DDP-induced muscle atrophy and improving cachexia symptoms. LIN has the potential to be developed as a drug against cancer cachexia.